Black soldier fly larvae oil can partially replace fish oil in the diet of the juvenile mud crab (Scylla paramamosain) - Yuhang Yang; Tingting Zhu; Min Jin; Xiangkai Li; Shichao Xie; Yuhui Cui; Qicun Zhou (Animal Nutrition)
An 8-week feeding trial was conducted to investigate the effects of replacing dietary fish oil (FO) with black soldier fly larval oil (BSFO) on growth performance, antioxidant and immune response, lipid metabolism and mitochondrial function of the juvenile mud crab. A total of 160 mud crabs (18.58 ± 0.02 g) were randomly distributed into five treatments spread across 160 aquaria. There were 4 replicates per treatment and 8 crabs per replicate. The basal diet (Control) contained 3% fish oil and fish oil was replaced with BSFO at 25%, 50%, 75%, and 100% in the remaining four treatments. The results showed that when the proportion of BSFO replacing FO was less than 50%, there were no significant differences in percent weight gain (PWG), specific growth rate (SGR) and feed efficiency (FE) between the experimental and the control groups (P > 0.05); however, PWG and SGR decreased as the percentage of substitution increased from 50% to 100% (P < 0.01). When the percentage of substitution was less than 50%, the expression levels of genes related to lipid synthesis and catabolism were significantly up-regulated and down-regulated, respectively (P < 0.05). When 25% and 50% FO were replaced with BSFO, the antioxidant and immune responses enhanced (P < 0.05), and antioxidant and immune-related enzyme activities and metabolite concentrations in the hemolymph and hepatopancreas significantly increased (P < 0.05), and the concentrations of malondialdehyde (MDA) and protein carbonyl (PC), and the apoptosis index in the hepatopancreas significantly decreased (P < 0.05). Moreover, mitochondrial function indexes in the hepatopancreas, such as mitochondrial DNA copy number and expression levels of energy metabolism-related genes were significantly up-regulated (P < 0.05). Hepatopancreas mitochondria were more abundant in crabs fed diets with 25% and 50% replacement of FO with BSFO, while adenosine triphosphate content was the highest in 25% FO replacement group (P = 0.003). In summary, the results of the present study demonstrated that the replacement of FO with BSFO at less than 50% (i.e. in-feed BSFO level of 1.5%) did not negatively affect the growth performance of mud crabs, and could improve the antioxidant capacity, immune response, and enhance mitochondrial function.